A porous fabric-based molecularly imprinted polymer for specific recognition of tetracycline by radiation-induced RAFT-mediated graft copolymerization. (October 2022) - Söylemez, Meshude Akbulut; Can, Hatice Kaplan; Bağda, Esra; Barsbay, Murat
Abstract: Despite technical and methodological advances, the selective separation of antibiotics from aqueous media remains a challenge. In this work, a novel molecularly imprinting polymer (MIP) with specific recognition sites was constructed by radiation-induced RAFT-mediated graft copolymerization of methacrylic acid (MAA) and ethylene glycol dimethacrylate (EGDMA) from PE/PP nonwoven fabric for tetracycline hydrochloride (TC) removal. Binding isotherm and kinetics were found to follow Freundlich and pseudo-second-order model, respectively. The as-synthesized molecularly-imprinted fabric exhibited excellent binding performance towards TC, with the maximum adsorption capacity and imprinting factor of 46.7 mg g −1 and 3.6, respectively. Moreover, it removed approximately 95% of TC from the aqueous media, also performed well in real environmental samples. For comparison purposes, MIPs obtained with conventional grafting performed significantly lower than those attained by RAFT-mediated grafting. After ten consecutive adsorption and desorption cycles, the fabric-based molecularly-imprinted material retained excellent stability and reusability with a performance loss of only 3.6%, which could facilitate its potential application on an industrial scale. Highlights: MIPs of tetracycline were prepared by radiation-induced RAFT polymerization. Conventional and RAFT-mediated methods were compared. A significantly better binding performance was achieved by RAFT method. An adsorption capacity of 46.7 mg g −1 was obtained. An imprinting factor of 4.32 was achieved.